Analisis Motivasi Mahasiswa dalam Belajar Fisika - Petri Reni Sasmita; Saiful Rachman; Zainal Hartoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to find out the comparative description of student motivation on the newly developed campus in physics learning with a more advanced campus. To get a description of the students motivation, as many as 87 students selected at random from three different campuses were surveyed using Science Motivation Questionnaire II. The science motivation questionnaire consists of five components of motivation: intrinsic motivation, self-determination, self-efficacy, career motivation, and grade motivation. The results show that there is no significant difference between student motivation on the newly developed campus and student motivation on a more advanced campus in physics learning. If it is seen based on the motivation component, it is known that there is no significant difference between all components of student motivation on the newly developed campus with student motivation on campus which is more advanced. Keyword: Physics Learning Motivation, Physics Learning, and Physics Education